The Students’ Perceptions of Artificial Intelligence (AI) in Higher Education: A Systematic Literature Review - Fujiono, Fujiono; Sakhiyya, Zulfa; Trisanti, Novia (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The fast development of Artificial Intelligence (AI) has a strong impact on the situation in higher education, especially on the way in which students learn, communicate, and interact with educational materials. The present study is a systematic literature review that examines 24 peer-reviewed articles published in 2020-2025 which concern on university students’ perceptions of AI technologies such as ChatGPT and generative AI tools. This research based on PRISMA methodology and the data acquired with the help of Publish or Perish application from the Scopus database, this study discusses the issues of acceptance and satisfaction, perceived benefits, ethical matters, and challenges regarding AI integration in higher education. The results show that most students perceive AI as a valuable tool that enhances efficiency, motivation, and learning autonomy. But there are still worries about overreliance, ethical use, academic integrity, and the potential erosion of critical thinking. The students’ perceptions and usage patterns are affected by contextual factors such as the field of study, gender, cultural background, and prior digital literacy influence. The review highlights the necessity of the participatory governance, systematized pedagogy, moral principles and collaborative policy making to make AI integration responsible and fair in higher education. After all, AI should be positioned not merely as a technical aid but as a transformative component of a humanistic and reflective learning environment.